Oskar-von-Miller Strasse 16 - Ohrt, Roberto 1954-; Riedel, Michael S. 1972-; Baumann, Daniel 1967- (Silverbridge, 2003)
This book is a documentation on the activities (exhibitions, books, events, records, posters, readings: work of the daily life of artists) that took place at Oskar von Müller Strasse 16, in Frankfort am Main, while it was occupied by a group of artists. The numerous documents and photographs, the result of experiments and accidents during the process of diffusion and communication of the artwork, illustrate the artistic project to which the four artists [Dennis Loesch, Hank Schmidt in der Beek, Michael S. Riedel, Niklas Schechinger] were committed. The text of the book is a transcription of the recordings of conversations describing the activities that took place there over 5 years. This book was offset printed in the U.S.A. (Royal Book Lodge)